ڕۆڵ و پێگەی ڕوسیا( ئیمپراتۆریی و سۆڤێتی) لە پەیمانی سایکس پیکۆ و کاریگەریی لەسەر پرسی کورد - مسته‌فا, ئارام علی (Sulaimani Journal for Humanities, 2018)
Abstract As dramatic changes in the political landscape of the Middle East and its borders were underway at the beginning of the twentieth century, both the Ottoman Empire and Iran were about to decline, mainly due to Russia‌s (and other European powers‌) intervention. This paper provides a historical background to Russia‌s stance on the political developments shaping the Middle East region where the world‌s great powers were in conflict with each other, and its role in the agreements and alliances followed to divide the remnants of the Ottoman Empire. This highlights how Russia influenced those changes during the disintegrating period of the Ottoman Empire. This paper sets out to consider the factors, both domestic and external, that determined Russia‌s attitudes in this period, mainly towards the direction of its alliances with other great powers and of course towards the Sykes-Picot agreement. It does so by examining aspects of Russia‌s policy in relation to its presence in the Middle East, both from a historical and a current perspective. The thesis draws a number of conclusions. Importantly, it is clear that domestic factors within Russia, mainly Russia's change of status, brought on by the revolutions took place in Russia and its withdrawal from the war, which resulted in removing Russia from inclusion. That was followed by the 1920 Sèvres Treaty which stripped the Ottomans of the remains of their empire, and divided Anatolia into European "spheres of influence”. However, the subsequent War of Independence changed the situation and enabled Mustafa Kemal, supported by the Soviet Union, to impose different terms in the Treaty of Lausanne in 1923, which led to the foundation of today‌s Turkey, and lost the few gains expected to be made by paragraphs 62, 63 and 64 of the Treaty of Sevres for the Kurdish People. Following the military, political, and diplomatic integration, the Kurdish people did not realize that they were an occupied homeland and had systematic rights and were deprived of their right to establish their own nation.